Analisis Pembelajaran Deep Learning di SDN 40 Mataram Tahun Ajaran 2025/2026 - Ilda Nurdiana; Syaiful Musaddat; Heri Setiawan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the implementation of deep learning that integrates the principles of mindful learning, meaningful learning, and joyful learning at the planning and implementation stages, as well as to identify the obstacles experienced by teachers in implementing deep learning. This research employed a qualitative approach using a case study design. The study was conducted during the even semester of the 2025/2026 academic year. The subjects of this study were all ten fourth-grade students, the fourth-grade teacher, and the principal of SDN 40 Mataram. Data were collected through observation, interviews, and documentation techniques. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings indicate that at the planning stage, the teacher had designed teaching modules, instructional materials, student worksheets, learning media, and evaluation instruments by integrating the three principles of deep learning: mindful learning, meaningful learning, and joyful learning. At the implementation stage, the teacher also applied these principles through interactive, contextual, and enjoyable learning activities. However, several obstacles were identified, including limited time, inadequate facilities and infrastructure such as limited internet access, and differences in students’ abilities and characteristics.